D-galactan II is an immunodominant antigen in O1 lipopolysaccharide and affects virulence in Klebsiella pneumoniae: implication in vaccine design - Hsieh, Pei-Fang; Wu, Meng-Chuan; Yang, Feng-Ling; Chen, Chun-Tang; Lou, Tzu-Chi; Chen, Yi-Yin; Wu, Shih-Hsiung; Sheu, Jin-Chuan; Wang, Jin-Town (Frontiers in Microbiology, 2014)
In the O1 strain of Klebsiella, the lipopolysaccharide (LPS) O-antigen is composed of D-galactan I and D-galactan II. Although the composition of the O1 antigen of Klebsiella was resolved more than two decades, the genetic locus involved in the biosynthesis of D-galactan II and the role of D-galactan II in bacterial pathogenesis remain unclear. Here, we report the identification of the D-galactan II-synthesizing genes by screening a transposon mutant library of an acapsulated Klebsiella pneumoniae O1 strain with bacteriophage. K. pneumoniae strain deleted for wbbY exhibited abrogated D-galactan II production; altered serum resistance and attenuation of virulence. Serologic analysis of K. pneumoniae clinical isolates demonstrated that D-galactan II was more prevalent in community-acquired pyogenic liver abscess (PLA) -causing strains than in non-tissue-invasive strains. WbbY homologs, WbbZ homologs, and lipopolysaccharide structures based on D-galactan II also were present in several Gram-negative bacteria. Immunization of mice with the magA-mutant (K1- O1) (that is, with a LPS D-galactan II-producing strain) provided protection against infection with an O1:K2 PLA strain. Our findings indicate that both WbbY and WbbZ homologs are sufficient for the synthesis of D-galactan II. D-galactan II represents an immunodominant antigen; is conserved among multiple species of Gram-negative bacteria and could be a useful vaccine candidate.